THE BUSINESS VALUE OF GOING GREEN: ASSESSING THE IMPACT OF ENVIRONMENTAL INNOVATION AND FINANCIAL INDICATORS IN INDONESIA’S ENERGY SECTOR COMPANIES - Adi, Maria Paramastri Hayuning; Hugoyantoro, Songgo Buwono; Kartikasary, Metya; Andini, Sophia (Universitas Jember, 2025)
ABSTRACTThis research aims to examine the effect of green innovation, profitability, and firm size on the firm value of Indonesian energy sector companies during the 2018–2023 period. The research is motivated by the growing importance of green innovation for encouraging environmental sustainability in energy sector companies. This research combine green innovation and financial indicators for increasing firm value. Using a sample of 66 data, the study employs panel regression analysis through Eviews software. The findings reveal that green product innovation have a significant positive impact on firm value. In contrast, green process innovation, profitability and firm size do not show a significant effect. The practical implications of this research related to the sustainability of energy sector companies are the importance of product innovation to optimize resources and minimize the negative impacts of carbon and pollution produced.Keywords: Firm Value; Green process innovation; Green product innovation; Profitability; Corporate Sustainability ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh green innovation, profitabilitas, dan ukuran perusahaan terhadap nilai perusahaan sektor energi yang terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2023. Penelitian ini dilakukan karena adanya pentingnya inovasi hijau terhadap keberlanjutan bisnis perusahaan sektor energi di Indonesia. Penelitian ini menggabungkan inovasi hijau dan kinerja keuangan untuk meningkatkan nilai perusahaan sektor energi di Indonesia Dengan menggunakan 66 sampel data, penelitian ini menggunakan analisis regresi data panel dengan software Eviews. Hasil penelitian ini menunjukkan bahwa green product innovation berpengaruh positif terhadap nilai perusahaan. Green process innovation, profitabilitas dan ukuran perusahaan tidak berpengaruh terhadap nilai perusahaan. Implikasi praktis dari penelitian ini terkait dengan keberlanjutan perusahaan sektor energi adalah pentingnya inovasi produk untuk optimalisasi sumber daya dan meminimalkan dampak negatif dari carbon dan polusi yang dihasilkan.Kata Kunci: Nilai Perusahaan; Inovasi Proses Hijau; Inovasi Produk Hijau; Profitabilitas; Keberlanjutan Perusahaan